Nursing care for critically ill adult patients with acute kidney injury undergoing dialysis treatment: an integrative review of the literature (Research, Society and Development, 2025)
Acute Kidney Injury (AKI) is a serious and multifaceted clinical condition that can appear suddenly and compromise kidney function, resulting in the accumulation of toxins and electrolytes in the body. The general objective of this study is to show the main challenges faced by nursing professionals in the care of critically ill patients with acute kidney injury undergoing dialysis treatment in order to highlight the scientific evidence present in the literature that can contribute to improving the quality of care. This is an Integrative Literature Review carried out in the databases PUBMED (US National Library of Medicine), Virtual Health Library Research Portal (VHL) and Scientific Electronic Library Online (SciELO) and Scopus and Lilacs (Latin American and Caribbean Literature in Health Sciences) where, after the inclusion and exclusion criteria, it was composed of 5 articles. The results showed that nurses have an essential role in assisting critical patients with acute kidney injury undergoing dialysis treatment, as they are responsible for preparing the hemodialysis unit, as well as guiding and helping the patient and their family to live with the treatment and the limitations imposed by the disease. It is also concluded that there is a need for greater training of nurses and nursing staff to align concepts, signs and symptoms, complications and interventions for the management of AKI in critical or non-critical patients, improving outcomes and minimizing morbidity and mortality.